2016
DOI: 10.1007/s00264-016-3203-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of recompression of cemented vertebrae after kyphoplasty for osteoporotic vertebral compression fractures

Abstract: The distance between polymethylmethacrylate and endplate is an important risk factor of recompression of cemented vertebrae after kyphoplasty for patients with osteoporotic vertebral compression fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Some scholars also found that the presence of non-PMMA-endplate-contact (NPEC) plays an important role in inducing the augmented vertebra recompression after PVA. Li et al [ 17 ] considered that the distance between the bone cement and the upper or lower endplates of the injured vertebrae can reflect the dispersion degree of bone cement more accurately. If the distance is too large, the risk of the augmented vertebra recompression will be increased, and the augmented vertebra recompression mainly occurs in the upper part of the vertebral body where it is not filled with bone cement.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars also found that the presence of non-PMMA-endplate-contact (NPEC) plays an important role in inducing the augmented vertebra recompression after PVA. Li et al [ 17 ] considered that the distance between the bone cement and the upper or lower endplates of the injured vertebrae can reflect the dispersion degree of bone cement more accurately. If the distance is too large, the risk of the augmented vertebra recompression will be increased, and the augmented vertebra recompression mainly occurs in the upper part of the vertebral body where it is not filled with bone cement.…”
Section: Discussionmentioning
confidence: 99%
“…The cases after PKP were particularly serious, which might be the result of different contact between bone cement surfaces in PKP balloons. There are many reasons for vertebral height loss after vertebral augmentation, for example, the severity of osteoporosis, the choice of surgical methods, the different surgical approaches, the different degrees of preoperative vertebral compression, the different distributions of bone cement, the different amounts of bone cement injection, or the existence of intravertebral cleft and other reasons [16][17][18][19][20][21][22][23]. Therefore, vertebroplasty alone is not appropriate for the treatment of OVF with severe compression and kyphosis.…”
Section: Compared With Previous Studiesmentioning
confidence: 99%
“…To us, the instrumented KP allows effective restoration on the central part of the vertebra. We did not notice any recollapse of cemented vertebra although we had a population with risk factors [20, 21]. In our worst case shown in Figure 5, no.…”
Section: Discussionmentioning
confidence: 72%